Balanço entre intemperismo químico e remoção do solo na bacia do Ribeirão Monjolo Grande, Ipeúna (SP), determinado por geoquímica fluvial - Spatti Júnior, Eder Paulo [UNESP]; Conceição, Fabiano Tomazini da [UNESP]; Guedes Júnior, Edvaldo [UNESP]; Pinto, Sérgio dos Anjos Ferreita [UNESP]; Pereira, Luis Henrique [UNESP] (Revista Brasileira de Geomorfologia, 2014)
This study aimed to evaluate the balance between chemical weathering and soil removal in the Monjolo Grande Stream basin, Ipeúna (SP), determined by river geochemistry. The results indicated a material dissolved transported of 6.33 t/km²/yr or 182.5 t/yr, due to chemical weathering processes of rocks in this watershed. In relation to sediment yield, it was obtained a flux of 31 t/km²/yr or 887 t/yr. The rates of chemical weathering and soil removal were 7 and 26 m/Ma, respectively, indicating a decrease in soil thickness in the Monjolo Grande basin under current climatic conditions. Simulation of different scenarios indicated a value of 2.65 m/Ma to rates of chemical weathering and soil removal will be equal. Furthermore, only in dry weather conditions the rates of chemical weathering will be greater than the soil removal.

Este trabalho teve como objetivo avaliar as taxas de intemperismo químico e remoção do solo na bacia do Ribeirão Monjolo Grande, Ipeúna (SP), determinadas por geoquímica fl uvial. Os resultados indicaram uma saída de material dissolvido de 6,33 t/km²/ano ou 182,5 t/ano devido aos processos de intemperismo químico das rochas nesta bacia hidrográfi ca. Em relação ao transporte de sedimentos, obteve-se um fl uxo de 31 t/km²/ano ou 887 t/ano. As taxas de intemperismo químico e remoção do solo foram de 7 e 26 m/Ma, respectivamente, indicando uma diminuição da espessura do solo na bacia do Ribeirão Monjolo Grande nas condições climáticas atuais. Simulações de diferentes cenários indicaram um valor de 2,65 m/Ma para que as taxas de intemperismo químico e a remoção do solo sejam iguais. Além disso, somente em condição climática seca as taxas de intemperismo químico serão maiores que a remoção do solo.
Balance between chemical weathering and soil removal in the Monjolo Grande Stream Basin, Ipeúna (sp), determined by river geochemistry
Keywords: Chemical weathering; Soil removal; Geomorphological evolution; River geochemistry; Environmental planning; Intemperismo químico; Remoção do solo; Evolução geomorfológica; Geoquímica fluvial; Planejamento ambiental